Productivity in a pandemic: effect of occupational health conditions and digital communications in the manufacturing industry - Hernández, Santos Ruíz; Martínez, Marco Antonio Díaz; Zubirías, Gabriela Cervantes (Brazilian Journal of Operations & Production Management, 2023)
Goal: The purpose of the study is to identify how Occupational Health conditions and digital communications are related to Productivity in times of pandemic in the manufacturing industry on the Tamaulipas and Texas border. Design / Methodology / Approach: An own instrument was designed for this study; it was applied to 104 informants with responsibility in productive areas in the manufacturing industry; the analysis was performed with SmartPLS. Results: a positive relationship was identified between independent variables of Digital Communications and Occupational Health conditions with respect to the dependent variable Productivity and they explain 69.8% (R2); workers gave more weight to the relationship between Occupational Health conditions with Productivity (51.5%), than to the relationship between Digital Communications and Productivity (39.2%). Limitations of the investigation: the study was analyzed from the perspective of the worker; participation was limited due to access issues due to the pandemic. Practical implications: the study shows an analysis procedure with PLS. Originality / Value: The article shows its relevance by presenting a model to establish relationships between worker health conditions and digital communications with an effect on labor productivity that will have an effect in the post-pandemic.